Simpson's Method of Discs for Measurement of Echocardiographic End‐Diastolic and End‐Systolic Left Ventricular Volumes: Breed‐Specific Reference Ranges in Boxer Dogs. (1st November 2013) - Smets, P.; Daminet, S.; Wess, G.
<x xml:space="preserve">Abstract</x> Background Boxer dogs are predisposed to congenital and adult onset cardiac diseases. Breed‐specific reference values for M‐mode and Doppler echocardiographic measurements previously have been established. Left ventricular (LV) end‐systolic (ESV) and end‐diastolic volumes (EDV) can be measured by M‐mode or two‐dimensional methods, such as Simpson's method of discs (SMOD). Reference ranges for SMOD‐derived LV volumes are lacking. Objectives To determine reference intervals for EDV and ESV in Boxer dogs. Animals Previously collected data from 85 healthy Boxers (37 males and 48 females) were used for analysis. Methods Simpson's method of discs‐derived EDV and ESV were measured using offline analysis by 1 observer, in both the right parasternal and the left apical views. Measurements were compared between both views and between male and female dogs using a t‐test. Reference intervals were established using the mean + 2 × SD. Results Measurements obtained from both views showed good agreement, and mean EDVI and ESVI, indexed to body surface area (BSA), were calculated. Reference intervals were 49–93 mL/m² for EDVI, and 22–50 mL/m² for ESVI. EDV and ESV were significantly higher in males compared with females, when indexing to BSA, but not when indexing to body weight. Conclusion and Clinical Importance The upper limit for ESVI exceeds the previously suggested cut‐off of 30 mL/m² for detection of systolic dysfunction. The reference intervals generated in this study should be useful clinically in the assessment of LV size and function in Boxer dogs.